Method mourning: Xunzi on ritual performance - Radice, Thomas (Philosophy East and West, 2017)
3 citations (Crossref) [2023-10-31]
Keywords: dept.his

Li (ritual) in early Confucianism - Radice, Thomas (Philosophy Compass, 2017)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-883-856-156-766, pop00371 tex.type: [object Object]
Keywords: dept.his

Painting on a White Foundation: Color, Countenance, and Performance in the Analects and Han Feizi - Radice, Thomas (From Surface to Meaning: Analyzing via Color)
Looking at colour can be a way not only to think within or about culture but also to probe the boundaries of cultural approaches. The "Cultural Turn," as it has been called, has made an impact across disciplines. In history, it replaced long-established explanatory models provided by Marxism and modernisation theory. Even fields like art history and literature, which always considered themselves allied to the arts rather than to the sciences, were reshaped by new understandings of culture - for instance, as a much larger system of meaning in which the works they studied were a part. But "culture" is notoriously murky, and its analytical use can obfuscate patterns of causality. This volume analyses how looking at colour can take us further.
Keywords: dept.his

Confucius and filial piety - Radice, Thomas (A Concise Companion to Confucius, 2017)
Keywords: dept.his